Online DE optimization for Fuzzy-PID controller of semi-active suspension system featuring MR damper - Ahmed, Hesham; As’arry, Azizan; Hairuddin, Abdul Aziz; Hassan, Mohd Khair; Liu, Yunyun; Onwudinjo, Erasmus Cufe Ujunwa (Institute of Electrical and Electronics Engineers, 2022)
In pursuit of a comfortable vehicle driving in different road profiles, intelligent methods are used to improve the vehicle’s suspension system. The semi-active suspension system outperformed other suspension systems because it contains an intelligent actuator that can give the appropriate force to dissipate unwanted vibration using intelligent and real-time controllers. In this paper, MR fluid damper with Fuzzy-PID controller is examined to be optimized using a modified DE algorithm. However, in the Fuzzy-PID controller, the fuzzy logic algorithm is used to auto-tune the PID controller, but it cannot be considered as a fully real-time controller since the fuzzy algorithm uses a previous knowledge base built offline. The offline design of the Fuzzy algorithm cannot cope with unexpected real-time vibrations occurred while driving a car in different road profiles. In this paper, a Fuzzy-DE-PID controller is proposed based on a modified DE algorithm to enhance the Fuzzy logic gains in order to increase vehicle semi-active suspension system performance. Simulation and experimental tests were conducted using the proposed controller with different disturbances to prove the proposed controller’s effectiveness. The results of the simulation and the experimental tests for the proposed controller showed an improvement in the vehicle’s ride comfort over the Fuzzy-PID and the passive system. We believe that using this proposed controller in any other real-time application will improve the performance to the highest levels without needing a previous knowledge base for designing a real-time Fuzzy-PID controller.